2022
DOI: 10.1111/wvn.12590
|View full text |Cite
|
Sign up to set email alerts
|

Health‐promoting behaviors and self‐efficacy among nursing students in times of uncertainty

Abstract: Background Nursing students are often faced with academic and personal stressors that threaten their Health‐Promoting Behaviors (HPB) and well‐being. Research on how living in a context of high political uncertainty can impact nursing students' HPB is limited. The aim of this study was to investigate the associations between HPB and self‐efficacy among nursing students in a context of high political uncertainty. Methods This was a cross‐sectional, descriptive study that included 120 undergraduate nursing stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…General Self-E cacy Scale [30] The GSES is a 10-item measure developed to assess an individual's subjective belief in themselves in coping with stressful situations. Participants were asked to respond to items on a Likert-type scale, ranging from 1 (not at all true) to 4 (exactly true).…”
Section: Methodsmentioning
confidence: 99%
“…General Self-E cacy Scale [30] The GSES is a 10-item measure developed to assess an individual's subjective belief in themselves in coping with stressful situations. Participants were asked to respond to items on a Likert-type scale, ranging from 1 (not at all true) to 4 (exactly true).…”
Section: Methodsmentioning
confidence: 99%
“…With its precision, cost-effectiveness, and dependability, AI offers several benefits. However, AI still has significant limits, particularly regarding medical applications (Doumit et al 2022 ; Abunadi et al 2022a ). There are now initiatives ongoing to enhance imaging mode comparability.…”
Section: Limitations Pitfalls and Future Challengesmentioning
confidence: 99%
“…Prevalence of depression and mental deterioration was also assessed in nursing students where it was concluded that self-efficacy among nursing students in a context of high political uncertainty, regardless of the pandemic, is often associated with health-promoting behaviors such as physical activity. 66,67 Studies that focused on hemato-oncological diseases…”
Section: Studies That Focused On Other Respiratory Diseases (Not Rela...mentioning
confidence: 99%